Solar-photoelectro-Fenton process as a cost-efficient alternative for removal of industrial dyes in sulfate and chloride media: Pilot scale evaluation - Martin O.A. Pacheco-Álvarez; Nelson Bravo-Yumi; Isabel Oller; Juan M. Peralta-Hernández (Applied Catalysis O: Open)
Advanced oxidation processes (AOPs) are widely recognized for their efficacy in treating contaminants across various environments. Notably, Boron-doped diamond electrodes (BDD) and mixed metal oxide electrodes (MMO) have emerged as promising tools for facilitating these processes. This study explores the potential of electrochemical processes for wastewater treatment, combining solar energy, electrochemical regeneration, and pollutant degradation. Pre-pilot scale experiments are conducted to assess scalability and treatment capacity. The study focuses on the removal of a dye tannery mixture using electrochemical oxidation (EO), and Fenton-Based processes such as electro-Fenton (EF), solar photoelectro-Fenton (SPEF), and Electro-Fenton-like (EFL), solar photoelectro-Fenton-like (SPEFL) processes based on the replacement of H2O2 by HClO, comparing BDD and MMO anodes. The research emphasizes the significance of supporting electrolyte media, current density, and Fe(II) concentration in the removal of a mixture of dyes (VMX) ((Violet H (VH), Violet SBL (VSBL), and Violet (S4B)). The findings highlight the potential of cost-effective MMO as an alternative to BDD for contaminant degradation. The study employs different analytical techniques, including UV–Vis spectrophotometry, HPLC, and COD analysis. An integrated approach with photovoltaic panels in a pre-pilot plant enhances energy efficiency and sustainability.